OGRANICZENIA IMPORTOWO-EKSPORTOWE. SYSTEM BARIER TECHNICZNYCH W HANDLU ŻYWNOŚCIĄ - Zalewski, Romuald I. (Wydział Prawa i Administracji UAM, 2000)
Still enlarging scope of technical barriers and their growing burdensome effect have been limited with, among others, an international agreement signed in 1994 within the framework of WTO. We mind here the Sanitary and Phitosanitary Measures (SPS) and Technical Barriers to Trade (TBT). The SPS are aimed principally at protection o f existence and health of human beings, animals and plants against the risk of widespreading o f pests and diseases being transmitted by animals and plants and, as well, against the risk involved with application of numerous toxic substances. The Author of the article classifies technical barriers in respect of particular policies of States, next - to the range of application and, finally, in respect of the kinds of the measures applied.
IMPORTS-EXPORTS LIMITATIONS. A SYSTEM OF TECHNICAL BARRIERS IN INTERNATIONAL FOOD TRADE